Online Media Construction in Reporting Rompi Putra Mulyono on detikcom and sindonews.com - Moh Hasbullah; Nur’annafi Farni Syam Maella (Institute of Advanced Knowledge and Science, 2025)
Mass media plays a significant roIe in shaping pubIic opinion by constructing reaIity through news framing. This study aims to analyze how Detik.com and Sindonews.com frame the symbolism of the